2012
DOI: 10.1016/j.ijsu.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of mesh repair for strangulated abdominal wall hernias

Abstract: Mesh hernioplasty is crucial to prevent recurrence, and it is safe to utilize it in repair of acutely incarcerated hernias even if associated with intestinal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
0
24
0
3
Order By: Relevance
“…The results showed low rates of wound infection (4.3%) and recurrence (4.3%), with a mean follow-up of 42 months. The authors therefore concluded that mesh hernioplasty is crucial to prevent recurrence and that it is safe for repairing acutely incarcerated hernias [ 45 ].…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed low rates of wound infection (4.3%) and recurrence (4.3%), with a mean follow-up of 42 months. The authors therefore concluded that mesh hernioplasty is crucial to prevent recurrence and that it is safe for repairing acutely incarcerated hernias [ 45 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…No significant difference was found in terms of postoperative morbidities, wound infection, and recurrence rate between the two groups. The authors therefore concluded that mesh hernia repair is crucial to prevent recurrence and that it is safe for repairing acutely incarcerated hernias, even in case of intestinal resection [ 45 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…reportan un porcentaje global de complicaciones del 35.7 % y una mortalidad del 5.9 % 3 . Otras series reportan una tasa de complicación del 30 % en las cirugías de urgencia y del 19 % en la cirugías electivas 11 . La necesidad de resección intestinal es un factor que aumenta la tasa de complicaciones y la mortalidad.…”
Section: Discussionunclassified
“…Many surgeons hesitate to use a mesh in cases of gangrenous strangulated intestines, because it may pose a potential risk for mesh infection. However, Abd Ellatif et al [ 8 ] divided patients with incarcerated hernia into two groups: those who underwent mesh hernioplasty with resection and anastomosis, and those who did not; there was no significant difference between the two groups in terms of wound infection and recurrence rates, and no patients had to undergo reoperation to remove the mesh. Considering these advantages, we suggest that laparoscopic mesh repair should be introduced more aggressively in cases of intestinal gangrene secondary to umbilical strangulated hernia.…”
Section: Discussionmentioning
confidence: 99%